2005
DOI: 10.1007/s00253-005-1979-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes stimulation in Aspergillus parasiticus by Lentinula edodes inhibits aflatoxin production

Abstract: Biosynthesis of aflatoxins, toxic metabolites produced by Aspergillus parasiticus, is correlated to the fungal oxidative stress and cell ageing. In this paper, the mechanism underlying the aflatoxin-inhibiting effect of the Lentinula edodes culture filtrates was studied by analysing their anti-oxidant activity and beta-glucan content. Mushroom beta-glucans are pharmacologically active compounds stimulating anti-oxidant responses in animal cells. L. edodes lyophilised filtrates stimulate A. parasiticus anti-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 29 publications
3
133
1
4
Order By: Relevance
“…Recently, mushrooms have been explored as potential control agents for AF contamination (Reverberi et al, 2005;Zjalic et al, 2006). Reverberi et al (2005) concluded that culture filtrate and purified -glucans from Lentinula edodes, an edible basidiomycetous mushroom native to East Asia, significantly inhibited AF production by A. parasiticus without affecting fungal growth. Their RT-PCR analyses of treated A. parasiticus mycelia showed a delay in activation of AF biosynthetic pathway genes aflR and norA as well as a simultaneous activation of hsf2-like, a transcription factor involved in oxidative stress responses.…”
Section: Mushrooms and Microfungi 421 β-Glucans And Culture Filtratmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mushrooms have been explored as potential control agents for AF contamination (Reverberi et al, 2005;Zjalic et al, 2006). Reverberi et al (2005) concluded that culture filtrate and purified -glucans from Lentinula edodes, an edible basidiomycetous mushroom native to East Asia, significantly inhibited AF production by A. parasiticus without affecting fungal growth. Their RT-PCR analyses of treated A. parasiticus mycelia showed a delay in activation of AF biosynthetic pathway genes aflR and norA as well as a simultaneous activation of hsf2-like, a transcription factor involved in oxidative stress responses.…”
Section: Mushrooms and Microfungi 421 β-Glucans And Culture Filtratmentioning
confidence: 99%
“…It has been shown that oxidative stress is a prerequisite and stimulatory factor for AF biosynthesis (Jayashree and Subramanyam, 2000;Reverberi et al, 2005). Oxidative stress is a result of exposure of fungal cells to ROS such as superoxide anion (O 2 · -), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (HO˙) and lipoperoxides (LOOH), which are formed from unsaturated fatty acids.…”
Section: Caffeic Acid: An Example Of Antioxidant-based Inhibition Of mentioning
confidence: 99%
“…Some studies suggested that mushrooms could be used also as inhibitors of mycotoxins production. Culture filtrates from Lentinula edodes and Trametes versicolor have revealed promising aflatoxin-inhibiting effects (Reverberi et al, 2005;Zjalic et al, 2006).…”
Section: Antifungal Activity Of Extracts and Compounds Isolated From mentioning
confidence: 99%
“…In testing the mechanisms involved in the aflatoxin-inhibiting effects of Lentinula edodes cultures, the authors demonstrated that these cultures act as an external stimulus affecting the anti-oxidant status in the fungal cells, which subsequently inhibits aflatoxin. Glucan present in cultures activates the transcription factors related to the anti-oxidant response 16 . Based on this study, glucan acts not "only" by absorption of mycotoxins but directly reduces aflatoxin production.…”
Section: Glucan and Mycotoxinsmentioning
confidence: 99%